High temperature recovery of radiation defects in tungsten and its effect on deuterium retention. (May 2020) - Zibrov, M.; Dürbeck, T.; Egger, W.; Mayer, M.
Highlights: The recovery of defects in W created by 9 MeV W ions to 1.1 dpa has been investigated. Annealing at 1600–1900 K leads to the formation of large vacancy clusters. Large vacancy clusters give rise to a desorption peak near 600 K. Complete recovery of radiation defects occurs after annealing at 2000 K. Abstract: The recovery of radiation defects in tungsten (W) due to post-irradiation isochronal (15 min) annealing at temperatures in the range of 1600–2100 K has been investigated. The defects were introduced in W (100) single crystals by irradiation with 9 MeV W ions to a maximum damage level of 1.1 dpa at 290 K. Vacancies and vacancy clusters in the samples were examined using positron annihilation lifetime spectroscopy. The defects were decorated with deuterium (D) by exposing the annealed samples to a low-flux (10 20  D/(m 2 s)), low-energy (10 eV/D) D plasma at a temperature of 450 K. The D concentration profiles in the samples were measured by D( 3 He, p) α nuclear reaction analysis and the D binding states in the defects were identified by thermal desorption spectroscopy. Annealing at 1600–1900 K resulted in the presence of mainly large vacancy clusters which gave rise to a single desorption peak near 600 K. The trapped D concentration in the sample annealed at 1600 K was 15% of that in the as-irradiated sample and decreased to 4% in the sample annealed at 1900 K. Annealing at 2000 K resulted in the complete recovery of radiation defects.